Electrocatalytic synthesis of hydrogen peroxide on Au-Pd nanoparticles: From fundamentals to continuous production - Pizzutilo, Enrico; Kasian, Olga; Choi, Chang Hyuck; Cherevko, Serhiy; Hutchings, Graham J.; Mayrhofer, Karl; Freakley, Simon J. (Chemical Physics Letters, 2017)
The electrochemical synthesis of hydrogen peroxide (H2O2) represents a promising alternative to the anthraquinone process, as it combines on-site chemical and electrical production. The design of selective electrocatalysts is challenging and is commonly based on the alloying of elements to generate a synergistic effect and increase activity. In the present work, we report the electrochemical activity of Au-Pd nanoparticles immobilized directly onto an electrode as a model to study H2O2 electrochemical synthesis from fundamentals to continuous production. The impact of composition on the oxygen reduction reaction (ORR), the selectivity, as well as the peroxide reduction and oxidation reactions (PROR) are studied. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Gold; Palladium; Hydrogen Peroxide; Electrocatalyst